Factors Affecting High-Oxygen Survival of Heterotrophic Microorganisms from an Antarctic Lake - Mikell, Alfred T. (1986)
We sought to determine factors relating to the survival of heterotrophic microorganisms from the high-dissolved-oxygen (HDO) waters of Lake Hoare, Antarctica. This lake contains perpetual HDO about three times that of normal saturation (40 to 50 mg liter(−1)). Five isolates, one yeast and four bacteria, were selected from Lake Hoare waters by growth with the membrane filter technique with oxygen added to yield dissolved concentrations 14 times that in situ, 175 mg liter(−1). One bacterial isolate was obtained from the microbial mat beneath the HDO waters. This organism was isolated at normal atmospheric oxygen saturation. The bacteria were gram-negative rods, motile, oxidase positive, catalase positive, and superoxide dismutase positive; they contained carotenoids. The planktonic isolates grew in media containing 10 mg of Trypticase soy (BBL Microbiology Systems)-peptone (2:1) liter(−1) but not at 10 g liter(−1). Under low-nutrient levels simulating Lake Hoare waters (10 mg liter(−1)), two of the planktonic isolates tested were not inhibited by HDO. Growth inhibition by HDO increased as nutrient concentration was increased. A carotenoid-negative mutant of one isolate demonstrated a decreased growth rate, maximal cell density, and increased cell lysis in the death phase under HDO compared with the parent strain. The specific activity of superoxide dismutase was increased by HDO in four of the five bacterial isolates. The superoxide dismutase was of the manganese type on the basis of inhibition and electrophoretic studies. The bacterial isolates from Lake Hoare possess several adaptations which may aid their survival in the HDO waters, as well as protection due to the oligotrophic nature of the lake.